2017
DOI: 10.1016/j.compstruct.2017.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Generation of controlled delaminations in composites using symmetrical laser shock configuration

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. b s t r a c tStructural Health Monitoring (SHM) is defined as the process of implementing a damage identification strategy for aerospace, civil and mechanical engineering infrastructures. SHM can be organized into five main steps: detection, localization, classification, quantification and prognosis. Our work considers SHM quantification level and in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The crossing of the two waves creates local high tensile stress which can result in damage at a through thickness depth if the energy level of the laser irradiation is high enough. More details about controlled delaminations in composites can be found in Ghrib et al (2017). (Ghrib et al, 2017).…”
Section: Application To Laser Shocks Delamination Experimental Datamentioning
confidence: 99%
“…The crossing of the two waves creates local high tensile stress which can result in damage at a through thickness depth if the energy level of the laser irradiation is high enough. More details about controlled delaminations in composites can be found in Ghrib et al (2017). (Ghrib et al, 2017).…”
Section: Application To Laser Shocks Delamination Experimental Datamentioning
confidence: 99%
“…where the indices r and l refer to the material respectively on the right and on the left of the area where the maximum tensile stress should be located, t li is the thickness of ply number i, ρ li the density of the ply, and Z li its shock impedance. Ghrib [21] has shown that by using this time delay, one can generate the maximum tensile stress in a specific location of the material, and for example generate a delamination in between two selected plies inside of a laminate structure. This technique has not yet been used to assess bonding quality on real aircraft parts.…”
Section: The Laser Shock Adhesion Test (Lasat)mentioning
confidence: 99%
“…Damage is introduced into samples (See Figure 2) in a calibrated way using LSWT and more particularly symmetrical laser shock configuration (See Figure 1). LSWT is chosen as an alternative to conventional damage generation techniques such as conventional impacts and Teflon inserts since it allows for a better calibration of damage in type, depth and size [3][4][5]. Four CFRP test coupons are considered.…”
Section: Test Structuresmentioning
confidence: 99%
“…The first one is kept in a healthy state. The second one was subjected to a symmetrical laser impact at 0 ns time delay and at 100% of the maximum energy of the two laser beams [5]. This resulted in approximately 7 mm diameter delamination which occurred at 1.1mm depth.…”
Section: Test Structuresmentioning
confidence: 99%